Knowledge and intake of functional foods by primary health care professionals from a legal amazon region, Brazil - Wadi, Jamal Mahmud Lucas (2017)
Backgroud: In order to counteract the incidence of chronic non-transmissible diseases the adoption of healthy food choices and functional foods are essencial. Objective: to evaluated knowledge and intake of functional foods by health professionals. Subjects and Methods: 45 health professionals (60% of the total) from the primary health care system from middle Araguaia, Legal Amazon, were studied. Dietary questionnaire evaluated knowledge of nutrition, food frequency, and intake frequency of functional foods. Results: The majority of people (64%) known the concept of functional foods. Functional foods with adequate dietary weekly intake was garlic, coffee, onions, and the common beans. The dietary intake of tomatoes and its products was 49% at least five days a week. Dietary intake of apples, cabagge, cheese and dairy products, grapes and grape juices was considerable, but insufficient. Considering Brazilian and regional foods, the dietary intake was considerable but unsatisfactory for bananas (Musa paradisiaca), Brazil or Cashew nuts (Bertholletia excelsa and Anacardium occidentale), â€œpequiâ€ (Caryocar brasiliense), red beet, papaya, orange, and river fishes. The dietary quality of health professionals should be improved by inclusion of both global, national, and regional foods and by reduction on the intake of fats, fatty foods, sweets, fried foods and meats.